Impact of the 2008–2009 financial crisis on the external and internal linkages of European frontier stock markets - Nikkinen, Jussi; Piljak, Vanja; Rothovius, Timo (Elsevier, 2020)
This study investigates the impact of the 2008–2009 financial crisis on (i) external linkages of European frontier stock markets (Croatia, Estonia, Romania, Slovakia and Slovenia) with the developed equity markets (the US, the UK, and Germany) and (ii) internal linkages within the frontier markets. The results demonstrate that both long- and short-run external linkages were strengthened during the crisis. The analysis of internal linkages reveals strong relationship only between the Croatian and Slovenian markets. However, the other frontier markets in the group were weakly linked, implying that European frontier stock markets may constitute a good alternative source of diversification benefits during crises periods.
Keywords: frontier market; diversification benefits; financial crisis; fi=Laskentatoimi ja rahoitus|en=Accounting and Finance|